Tunable hydrogels for controlling phenotypic cancer cell states to model breast cancer dormancy and reactivation. (September 2019) - Pradhan, Shantanu; Slater, John H.
Abstract: During metastasis, disseminated tumor cells (DTCs) from the primary tumor infiltrate secondary organs and reside there for varying lengths of time prior to forming new tumors. The time delay between infiltration and active proliferation, known as dormancy, mediates the length of the latency period. DTCs may undergo one of four fates post-infiltration: death, cellular dormancy, dormant micrometastasis, or invasive growth which, is in part, mediated by extracellular matrix (ECM) properties. Recapitulation of these cell states using engineered hydrogels could facilitate the systematic and controlled investigation of the mechanisms by which ECM properties influence DTC fate. Toward this goal, we implemented a set of sixteen hydrogels with systematic variations in chemical (ligand (RGDS) density and enzymatic degradability) and mechanical (elasticity, swelling, mesh size) properties to investigate their influence on the fate of encapsulated metastatic breast cancer cells, MDA-MB-231. Cell viability, apoptosis, proliferation, metabolic activity, and morphological measurements were acquired at five-day intervals over fifteen days in culture. Analysis of the phenotypic metrics indicated the presence of four different cell states that were classified as: (1) high growth, (2) moderate growth, (3) single cell, restricted survival, dormancy, or (4) balanced dormancy. Correlating hydrogel properties with the resultant cancer cell state indicated that ligand (RGDS) density and enzymatic degradability likely had the most influence on cell fate. Furthermore, we demonstrate the ability to reactivate cells from the single cell, dormant state to the high growth state through a dynamic increase in ligand (RGDS) density after forty days in culture. This tunable engineered hydrogel platform offers insight into matrix properties regulating tumor dormancy, and the dormancy-proliferation switch, and may provide future translational benefits toward development of anti-dormancy therapeutic strategies.